THE URGENCE OF REPUTATION RISK MANAGEMENT OF THE AMIL ZAKAT INSTITUTION - Mutafarida, Binti; Sariati, Ning Purnama; Sulistyowati, Sulistyowati (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
The occurrence of the covid-19 outbreak shows the social spirit of the community is getting bigger, this is shown by the increase in social funds collected both individually and through official ziswaf collecting institutions. The number of ziswaf institutions in Indonesia compete with each other to collect social funds in the community. This competition requires LAZIS to compete in implementing risk management inherent in its operations, including reputation management. Reputation is one of the considerations of the community in entrusting the distribution of funds through the ziswaf institution. Reputation management is a collection of images owned by the public related to Lazis, both the general public and stakeholders. A positive reputation can have an impact that more and more people entrust their funds to be channeled through ziswaf and conversely the worse the reputation will reduce the level of public trust in the distribution of social funds through ziswaf institutions. The International Working Group on Zakat Core Principle theory becomes the analytical knife in this study, where the IWGZCP has three indicators in the application of reputation risk management in ziswaf institutions and the theory of Louisot JP., and Rayner J., where there are seven things that need to be considered in managing reputation. The Mix Approuch approach used in this study is a literature review and a phenomenological approach, where the results obtained are that reputation is a very important factor to be applied by ziswaf institutions, one of which is transparency in all forms of reports published through social media owned or through the official website. owned by each lasis. 3 things and 7 things that are applied make people's trust increases in choosing lasis.